CASE REPORT: CENTRAL PRECOCIOUS PUBERTY IN A CHILD WITH BLOCH-SULZBERGER SYNDROME. - Oliveira, Isabella Carvalho; de Oliveira, Anselmo Fernandes Rezende; da Costa, Pedro Henrique Alves; Guedes, Virgílio Ribeiro; Amorim, Patrícia Bastos (Revista de Patologia do Tocantins, 2015)
Objective: To describe a case of a child with IncontinentiaPigmenti associated with precocious puberty. Case description: a 1 year 7 months old female babywas taken by her parents to a medical appointment because of an aggravation of skin spots with a latté color disseminated throughout the body, which appeared when the child was five months old. The mother also referred premature thelarche and premature pubarche since the child was three months old. Comments: Precocious puberty is defined as the development of secondary sexual characteristics before the age of eightin girls and nine in boys. The Bloch-Sulzberger syndrome, or Incontinentia Pigmenti, is a disorder linked to the X chromosome that affects the skin, eyes, teeth and may be associated with neurological deficits. As much as this specific syndrome involves multiple organs and systems, there was no association with an endocrine disorder.